Taste Disturbance Due to Cochlear Implant Stimulation. Issue 8 (September 2016) - Shayman, Corey S.; Middaugh, Jessica L.; Hullar, Timothy E.
Abstract : Objective: To characterize stimulation of taste fibers in the facial nerve following cochlear implantation. Patient: A 34-year old presented with reversible dysgeusia following activation of a cochlear implant. Intervention: Reprogramming targeted to specific offending electrodes reduced symptom intensity. Computed tomography demonstrated dehiscence of the bone separating the labyrinthine segment of the facial nerve and the basal turn of the cochlea in proximity to the electrode array. Results: Dysgeusia was attributed to stimulation of taste fibers in the facial nerve by electrodes 13 to 16 of the cochlear implant array located in the superior-most portion of the basal turn. Conclusions: Dysgeusia following cochlear implant activation has not previously been reported. This likely results from stimulation of taste fibers through dehiscence of the bone separating the labyrinthine segment of the Fallopian canal and the basal turn of the cochlea. While in some cases of apparent dehiscence there may be thin bone present, recognition of this potential anatomic feature may influence the choice of which ear and which electrode design to implant.